Petunjuk Alquran Tentang Belajar Dan Pembelajaran - Syeh Hawib Hamzah (UIN Sultan Aji Muhammad Idris Samarinda, 2009)
Al-qur’an is normative source in Islamic education. Al-qur’an consists of the importance of learning and study. It’s described from many verses of Al-qur’an which explain about knowledge. For instance, the first verse that stated “iqra” which is in Indonesian language means “bacalah”. Furthermore, Al-qur’an contains the methods used in learning in order to ease people who want to study. Those kinds of methods are discussion method, tarhib wa targhib method, story method, learn by example method, and also practice and repeating method.